EKSPLORASI BAKTERI LOKAL PENGHASIL ANTIMIKROBA DI CAGAR ALAM TANJUNG API TELUK TOMINI SULAWESI TENGAH, INDONESIA - Alwi Millang; Widiawati; Umrah; Orryani Lambui (Biology Department, Mathematics and natural science, Tadulako University, 2021)
ABSTRACT Tanjung Api Nature Reserve is a headland located in Tomini Bay Ampana District Tojo Una-Una Regency, Central Sulawesi Province. This study aims to obtain local bacteria isolates as antimicrobial producers. The method used in this research is purposive sampling and screening method using